Study the Effect of MgO Addition on Some of Physical Properties of ZnO - Abd-Al Hassan, S. k. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Different percents(1.0,2.5,5.0 and 10)wt%of MgO powders were added to ZnO powder to study their effects on the physical properties of ZnO.Density, porpsity and water absorption of ZnO were decreased as MgO weigth percentage content increased. The values of vickers hardneess have double values especially at 1.0 wt % of MgO.